Physiological and Biochemical Responses of Pepper (Capsicum annuum L.) Seedlings to Nickel Toxicity - Altaf, Muhammad Ahsan; Hao, Yuanyuan; He, Chengyao; Mumtaz, Muhammad Ali; Shu, Huangying; Fu, Huizhen; Wang, Zhiwei (Frontiers in Plant Science, 2022)
Globally, heavy metal pollution of soil has remained a problem for food security and human health, having a significant impact on crop productivity. In agricultural environments, nickel (Ni) is becoming a hazardous element. The present study was performed to characterize the toxicity symptoms of Ni in pepper seedlings exposed to different concentrations of Ni. Four-week-old pepper seedlings were grown under hydroponic conditions using seven Ni concentrations (0, 10, 20, 30, 50, 75, and 100 mg L–1 NiCl2. 6H2O). The Ni toxicity showed symptoms, such as chlorosis of young leaves. Excess Ni reduced growth and biomass production, root morphology, gas exchange elements, pigment molecules, and photosystem function. The growth tolerance index (GTI) was reduced by 88-, 75-, 60-, 45-, 30-, and 19% in plants against 10, 20, 30, 50, 75, and 100 mg L–1 Ni, respectively. Higher Ni concentrations enhanced antioxidant enzyme activity, ROS accumulation, membrane integrity [malondialdehyde (MDA) and electrolyte leakage (EL)], and metabolites (proline, soluble sugars, total phenols, and flavonoids) in pepper leaves. Furthermore, increased Ni supply enhanced the Ni content in pepper’s leaves and roots, but declined nitrogen (N), potassium (K), and phosphorus (P) levels dramatically. The translocation of Ni from root to shoot increased from 0.339 to 0.715 after being treated with 10–100 mg L–1 Ni. The uptake of Ni in roots was reported to be higher than that in shoots. Generally, all Ni levels had a detrimental impact on enzyme activity and led to cell death in pepper seedlings. However, the present investigation revealed that Ni ≥ 30 mg L–1 lead to a deleterious impact on pepper seedlings. In the future, research is needed to further explore the mechanism and gene expression involved in cell death caused by Ni toxicity in pepper plants.